Nephrotoxicity assessment of podophyllotoxin-induced rats by regulating PI3K/Akt/mTOR-Nrf2/HO1 pathway in view of toxicological evidence chain (TEC) concept - Kong, Jiao; Kui, Hongqian; Tian, Yue; Kong, Xianbin; He, Tao; Li, Qingbo; Gu, Chunyu; Guo, Jinhe; Liu, Chuanxin (Ecotoxicology and environmental safety, 2023)
Adverse reactions to traditional Chinese medicine have hindered the healthy development and internationalization process of the traditional Chinese medicine industry. The critical issue that needs to be solved urgently is to evaluate the safety of traditional Chinese medicine systematically and effectively. Podophyllotoxin (PPT) is a highly active compound extracted from plants of the genus Podophyllum such as Dysosma versipellis (DV). However, its high toxicity and toxicity to multiple target organs affect the clinical application, such as the liver and kidney. Based on the concurrent effects of PPT's medicinal activity and toxicity, it would be a good example to conduct a systematic review of its safety. Therefore, this study revolves around the Toxicological Evidence Chain (TEC) concept. Based on PPT as the main toxic constituent in DV, observe the objective toxicity impairment phenotype of animals. Evaluate the serum biochemical indicators and pathological tissue sections for substantial toxic damage results. Using metabolomics, lipidomics, and network toxicology to evaluate the nephrotoxicity of PPT from multiple perspectives systematically. The results showed that PPT-induced nephrotoxicity manifested as renal tubular damage, mainly affecting metabolic pathways such as glycerophospholipid metabolism and sphingolipid metabolism. PPT inhibits the autophagy process of kidney cells through the PI3K/Akt/mTOR and Nrf2/HO1 pathways and induces the activation of oxidative stress in the body, thereby causing nephrotoxic injury. This study fully verified the feasibility of the TEC concept for the safety and toxicity evaluation of traditional Chinese medicine. Provide a research template for systematically evaluating the safety of traditional Chinese medicine. [Display omitted] •Continuous exposure to podophyllotoxin for 4 days can cause nephrotoxicity in rats.•The mechanism of PPT-induced nephrotoxicity was investigated for the first time.•The TEC concept was expanded and practiced, and we defined the concept of GTEA.•It provides a tool for systematically evaluating the safety and toxicity of TCM.